Supply Chian Risk Management in China -- A cae study of two manufacturing companies in China - Sui, Zhiyu (2013)
In the currently business world, companies face high competitive pressures from trends of global outsourcing, varieties of product types, shorter products life cycle. This result in increasing complexity of supply chain network and a high level of supply chain risks. In addition, supply chain risk management become vital and can be used to mitigate supply chain risks. There are many previous research focused on supply chain risk management in developed countries, but not many take depth research on a specific country or in a developing countries, especially the world factory – China, who has different in context of government policies, regulations, environment, and culture, which can change the framework of supply chain risks and risk management.